Optimization of wear parameters of aluminium matrix composites (LM6/Fly Ash) using Taguchi technique. (2021) - Udaya Prakash, J.; Divya Sadhana, A.; Ananth, S.; Arun Pillai, K.V.
Abstract: Wear behavior of aluminum matrix composites (AMCs) has been studied. AMCs consist of LM6 aluminum alloy as the matrix material and 3%, 6% and 9% of particulate fly ash by weight as the reinforcement material. Stir casting process was used to produce the AMCs. Wear tests were performed on a pin on a disc machine according to ASTM G99 – 05 specifications. Taguchi's methodology was implemented and L27 orthogonal array was selected for conducting the wear tests. The main objective is to use S / N ratio and analysis of variance to investigate the effect of load, sliding distance, sliding speed and weight percentage of reinforcement on specific wear rate (SWR). Load has the largest statistical impact on SWR (24.31%) followed by sliding distance (16.43%). To validate the results of the experiments, confirmation tests were performed.